The Role of Quality Human Capital and Planning Strategies in Achieving Event Sustainability in Lombok - Surayyal Hizmi; Satria Rusdy Wijaya; Nawawi (Politeknik Pariwisata Lombok, 2022)
Background: The success of implementing a sustainable event in a tourist destination cannot be separated from the influence of the quality of human resources (human capital) and planning strategies. However, studies of the interdependence between human capital and planning strategies in achieving successful implementation of sustainable events, especially on the island of Lombok, are still limited Methodology: This study aims to examine and analyze the extent to which aspects of human capital and strategic planning play a role in optimizing the implementation of events on the island of Lombok. The method used is a literature review from journals and trusted sources, as well as problem analysis through in-depth interviews with resource persons involved in the implementation of the event. The focus of this study is to compare tourism events, namely the Bali Arts Festival (PKB) in Bali and the Bau Nyale Festival in Lombok Findings: The results of in-depth interviews with several sources show that the PKB held on the island of Bali is still superior in the number of enthusiasts and concepts than the implementation of the Bau Nyale Festival on the island of Lombok. This is shown by the length of the PKB implementation and the age of the PKB which has been going on in the past 4 decades ago. In addition, the main factor that affects the sustainability of PKB is the quality of human resources in the tourism sector on the island of Bali, which is superior to the island of Lombok, so as to be able to formulate effective and creative planning in packaging the event. To achieve the sustainability of the event in Lombok, it is necessary to increase human capital and appropriate planning strategies through counselling, training, and the availability of Meeting study programs. Conclusion: Human capital and strategic planning play important roles for achieving sustainable event to support the development of tourist destination. The result of comparison study between Bali Arts Festival and Bau Nyale Festival shows that Bali Arts Festival was greater than Bau Nyale festival in terms of numbers of visitors and implementation concepts. This was proved by the length of festival and number of tourists visiting. Bali Arts Festival has been run for about 40 years, while Bau Nyale Festival has been currently occurred in Lombok. In addition, human capital in Bali Arts Festival was greater showing in how well management applied during the event, so that, it is able to plan with a precise strategy in achieving sustainable event.